Antitumour bioactive peptides isolated from marine organisms. (16th October 2017) - Xing, Haibo; Tong, Mengting; Jiang, Nanyu; Zhang, Xiaomin; Hu, Hong; Pan, Hongming; Li, Da
Summary: Marine organisms are an important source of antitumour active substances. Thus, pharmaceutical research in recent years has focused on exploring new antitumour drugs derived from marine organisms, and, many peptide drugs with strong antitumour activities have been successfully extracted. Based on different mechanisms, this paper reviews the research on several typical antitumour bioactive peptides in marine drugs and the latest progress therein. Additionally, the development prospects for these antitumour bioactive peptide‐based drugs are discussed so as to provide a reference for future research in this field.